Book Review: F. KONDYLI - V. ANDRIOPOULOU - E. PANOU - M. B. CUNNINGHAM (edd.), Sylvester Syropoulos on Politics and Culture in the Fifteenth Century Mediterranean. Themes and Problems in the Memoirs, Section IV, Αshgate 2014 - PERRA, Photeine (Byzantina Symmeikta, 2016)
Book Review: Fotini KONDYLI - Vera ANDRIOPOULOU - Eirini PANOU - Mary B. CUNNINGHAM (edd.), Sylvester Syropoulos on Politics and Culture in the Fifteenth Century Mediterranean. Themes and Problems in the Memoirs, Section IV, [Birmingham Byzantine and Ottoman Studies, volume 16], Ashgate, 2014, pp. 248, ISBN: 978-1-4094-3966-0